THE EFFECTIVENESS OF FUNERAL RETRIBUTION PAYMENTS IN DKI JAKARTA - Prihanto, Hendi; Usmar , Usmar; Selfiani , Selfiani; Adwimurti, Yudhistira (International Journal of Application on Economics and Business, 2023)
Management of cemetery land is a problem that is currently being experienced in the DKI Jakarta area, for this reason the research aims to analyze the influence of the e-Retribution Payment System, Government Socialization, Compulsory Retribution Literacy on the Effectiveness of Retribution Payments. The research uses a quantitative approach which uses a questionnaire as a data collection technique, processing statistical data using the Smart PLS application. The research population was TPU in the South Jakarta area, with burial samples in a number of TPU, namely: Kampung Kandang, Jeruk Purut, Tanah Kusir and Menteng Pulo. The unit of analysis for this research is the community as the heirs of families buried in the area. The results of the study prove that empirically the electronic levy payment system and outreach carried out by the government have a positive and significant effect on the effectiveness of retribution payments, while levy compulsory literacy has no significant effect on the effectiveness of retribution payments.